Synthesis of legonmycins A and B, C(7a)-hydroxylated bacterial pyrrolizidines - Lewis, Wilfred J. M.; Shaw, David M.; Robertson, Jeremy (Beilstein Journal of Organic Chemistry, 2021)
A one-flask, two-step procedure from 3-amino-2-methyl-5,6,7,7a-tetrahydro-1H-pyrrolizin-1-one affords the Streptomyces secondary metabolites legonmycins A and B – three operations overall from methyl N-Boc-prolinate. The key step proceeds in each case via N,O-diacylation, then selective oxidative hydrolysis of the intermediate bicyclic pyrrole and establishes a precedent for the synthesis of related C(7a)-hydroxylated pyrrolizidines.
Keywords: acyloxypyrroles; bacterial pyrrolizidines; cyanoketones; legonmycin; vinylogous ureas